The biology of reproduction of the Tete veld rat, Aethomys ineptus and the Namaqua rock mouse, Aethomys namaquensis (Rodentia: Muridae) - Bennett, Nigel Charles (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2006.